Intervention of the Cimahi City MSME Community through Collaborative and Participatory Training in Supporting Business Sustainability - Sodikin, Sodikin; Ardiwinata, Jajat Sudrajat; Komar, Oong; Sukmana, Cucu; Mutamam, Mohamad Hadi Ali; Inoue, Hiromu (Indonesian Journal of Adult and Community Education, 2025)
This study aims to analyze community interventions for Micro, Small, and Medium Enterprises (MSMEs) in Cimahi City through collaborative and participatory training to support business sustainability. The focus of the study is directed at identifying structural and functional problems faced by MSMEs in the context of collaboration and participation, as well as exploring how community-based training contributes to building business capacity and resilience. This study uses a qualitative approach with data collection techniques through observation, in-depth interviews, and Focus Group Discussions (FGD) involving MSME actors and community facilitators in Cimahi City. The results of the study showed three main findings: (1) The identification of various business problems stemming from the low intensity of collaboration and lack of active participation of MSMEs in community activities; (2) The mapping of solutions based on local needs, including through the implementation of collaborative training, strengthening business networks, and optimizing the role of the community as a shared learning space; and (3) Proven community contribution in encouraging the sustainability of MSME businesses through the process of collective learning, sharing experiences, and increasing managerial capacity and business innovation. The impact of this study shows that collaborative and participatory training approaches facilitated by the community have high effectiveness in strengthening the sustainability of MSMEs. This intervention model can be replicated in other regions as a systematic and sustainable local empowerment-based development strategy.